Eco-Enzyme Project-Based Learning in the Elementary School: Improving SDGs 12.5 Waste Management Knowledge - Azmi Al-Bahij; Nurul Umrotullatifah; Lativa Qurrotaini; Apri Utami Parta Santi (Jurnal Ilmiah Sekolah Dasar, 2024)
Improving school waste management knowledge is one way to make schools cleaner and more comfortable. Based on the analysis, there is still much garbage scattered in the elementary school environment, even though there is material about the rights and obligations towards the environment contained in the learning material in the classroom. Based on the analysis, less varied learning models are used during learning to improve waste management knowledge on the material of rights and obligations towards the environment. This study aims to analyze the Eco-enzyme project-based learning (PjBL) learning model's role in improving waste management knowledge of SDGs 12.5. The research design applied is a true experiment using the fifth grade, consisting of two classes, namely, class 5A, which acts as an experimental class, and class 5B, which acts as a control class. The data collection techniques applied were interviews, tests, and documentation. The data analysis techniques used were paired t-test and determination coefficient test. The results showed that the Eco-enzyme project-based learning (PjBL) model played a role in increasing knowledge of waste management SDGs 12.5 based on the results of the paired t-test and the coefficient of determination, a significant increase in the post-test results of waste management knowledge SDGs 12.5 in the experimental class of 81.6%. The project-based learning (PjBL) eco-enzyme learning model increases knowledge of waste management SDGs 12.5.